2016
DOI: 10.1038/srep28855
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Culture of Aligned Skeletal Myotubes on Micromolded Gelatin Hydrogels

Abstract: In vitro models of skeletal muscle are critically needed to elucidate disease mechanisms, identify therapeutic targets, and test drugs pre-clinically. However, culturing skeletal muscle has been challenging due to myotube delamination from synthetic culture substrates approximately one week after initiating differentiation from myoblasts. In this study, we successfully maintained aligned skeletal myotubes differentiated from C2C12 mouse skeletal myoblasts for three weeks by utilizing micromolded (μmolded) gela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
145
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(159 citation statements)
references
References 58 publications
9
145
0
Order By: Relevance
“…Although future studies will be required to enhance and optimize culture conditions, our present results provide a proof of concept of the feasibility of the use of micropatterned gelatin–GP biomaterial to generate in vitro cultures of unidirectionally aligned contracting primary myotubes where electrophysiological studies can be performed. A recent study showed that micropatterned gelatin hydrogels, realized with different cross‐linker and smaller strip size, are more effective in driving the growth and orientation of C2C12 myotubes in in vitro long‐term cultures, when compared to the commonly used extracellular microcontact printed PDMS . Although we did not analyze our cells after 3 weeks in culture, we could assume that our system may be as effective as this, and find application for in vitro studies on muscle development and disease, and on chronic drug testing.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although future studies will be required to enhance and optimize culture conditions, our present results provide a proof of concept of the feasibility of the use of micropatterned gelatin–GP biomaterial to generate in vitro cultures of unidirectionally aligned contracting primary myotubes where electrophysiological studies can be performed. A recent study showed that micropatterned gelatin hydrogels, realized with different cross‐linker and smaller strip size, are more effective in driving the growth and orientation of C2C12 myotubes in in vitro long‐term cultures, when compared to the commonly used extracellular microcontact printed PDMS . Although we did not analyze our cells after 3 weeks in culture, we could assume that our system may be as effective as this, and find application for in vitro studies on muscle development and disease, and on chronic drug testing.…”
Section: Discussionmentioning
confidence: 97%
“…A recent study showed that micropatterned gelatin hydrogels, realized with different cross-linker and smaller strip size, are more effective in driving the growth and orientation of C2C12 myotubes in in vitro long-term cultures, when compared to the commonly used extracellular microcontact printed PDMS. 59 Although we did not analyze our cells after 3 weeks in culture, we could assume that our system may be as effective as this, and find application for in vitro studies on muscle development and disease, and on chronic drug testing.…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐defining topographical features at the time of hydrogel crosslinking, via pre‐formed template micro‐molding, could constitute fitting alternatives that can conjugate topography and ECM composition. [ 89,101,102 ] However, these strategies are limited by confining the patterning process within the manufacturing timeframe. Hence, approaches that can enable on‐demand patternability are being pursued, such as spatially controlled hydrogel photodegradation, but are still restricted to either fully synthetic PEG‐based networks or more recently, to hybrid PEG/gelatin combinations.…”
Section: Resultsmentioning
confidence: 99%
“…Hsiao et al (2009) reported a DNA oligonucleotide based micropatterned glass substrate for selective adherence and subsequent differentiation of primary myoblasts. Bajaj et al (2011) Antigny, Koenig, Bernheim, & Frieden, 2013;Bettadapur et al, 2016;Shahini et al, 2018). PDMS membranes were utilised for micropatterning C2C12 cells by Huang, Lee, and Li (2010) to study myoblast alignment.…”
Section: Introductionmentioning
confidence: 99%
“…Zatti et al (2012) went a step further by micropatterning C2C12 cells on hydrogels with tissue like stiffness and elucidating the importance of secretory factors in myogenesis. Furthermore, several other studies have utilized morphometric based characterization parameters, for example, myotube width, fusion index, and nuclear distribution for assessing differentiation and myotube formation (Agley, Velloso, Lazarus, & Harridge, 2012;Antigny, Koenig, Bernheim, & Frieden, 2013;Bettadapur et al, 2016;Shahini et al, 2018). In addition, techniques like 2D FFT analysis and orientation order parameter (OOP) have been applied for assessing alignment in muscle tissues (Bajaj, Rivera, Marchwiany, Solovyeva, & Bashir, 2014;Drew, Eagleson, Baldo Jr., Parker, & Grosberg, 2015;Feinberg et al, 2012).…”
Section: Introductionmentioning
confidence: 99%